Solvent‐free synthesis of polyols from 1‐butene metathesized palm oil for use in polyurethane foams. Issue 23 (26th February 2016) - Pillai, Prasanth K. S.; Li, Shaojun; Bouzidi, Laziz; Narine, Suresh S.
ABSTRACT: Green Polyols were synthesized from a 1‐butene cross metathesized palm oil (PMTAG) using a green, solvent free epoxidation and hydroxylation pathway. The synthetic strategy was adapted to control the degree of double bond epoxidation and ultimately the hydroxyl value of the polyols. The polyols comprised diol and tetrol monomers with terminal hydroxyl groups content as high as ∼18 mol %, and achieved hydroxyl values between 83 and 119 mg KOH g −1 . Functional Rigid and highly flexible foams were prepared from two designer Green Polyols. The foams presented a high thermal stability ( T on of degradation of ∼270 °C), suitable glass transition temperatures (∼−12 °C and ∼50 °C) and compressive strength (0.21 MPa at 10% strain and ∼1 MPa at 10% strain for the flexible and rigid foams, respectively) which are superior to existing lipid‐based counterparts. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43509. Abstract :